2001
DOI: 10.1590/s0004-282x2001000500017
|View full text |Cite
|
Sign up to set email alerts
|

Acidente vascular cerebral em pacientes jovens: análise de 164 casos

Abstract: RESUMO -Realizamos análise epidemiológica de 164 pacientes com AVC, cujo primeiro episódio ocorreu entre 15 e 49 anos de idade através de um estudo retrospectivo de pacientes ambulatoriais. O principal tipo de apresentação foi AVC isquêmico (AVCI) em 141 pacientes, ocorrendo AVC hemorrágico (AVCH) em16 casos e 7 pacientes com trombose venosa. A presença de fatores de risco aterotrombóticos foi prevalente, em 48,22% dos pacientes com AVCI sendo que a hipertensão arterial sistêmica (HAS), nos casos de AVCH, foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0
40

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 25 publications
3
7
0
40
Order By: Relevance
“…However, our experience in São Paulo corroborates the findings of Zétola et al in Curitiba, Brazil, who found higher percentages of atherothrombotic stroke in young adults associated with high prevalence of arterial hypertension, smoking, hypercholesterolemia, diabetes mellitus and alcohol abuse 35,36 . Thus, for reducing the burden of stroke also in young populations, it seems very cost-effective prioritizing interventions targeting control of modifiable risk factors, especially in developing countries and minorities in high income nations 37 .…”
Section: Large-artery Atherosclerosissupporting
confidence: 91%
“…However, our experience in São Paulo corroborates the findings of Zétola et al in Curitiba, Brazil, who found higher percentages of atherothrombotic stroke in young adults associated with high prevalence of arterial hypertension, smoking, hypercholesterolemia, diabetes mellitus and alcohol abuse 35,36 . Thus, for reducing the burden of stroke also in young populations, it seems very cost-effective prioritizing interventions targeting control of modifiable risk factors, especially in developing countries and minorities in high income nations 37 .…”
Section: Large-artery Atherosclerosissupporting
confidence: 91%
“…In this study the majority of patients at the time of admission showed a moderate stroke severity according to the NIHSS, which is in consonance with Rena et al 9 2014, a study conducted on a stroke unit in Italy, which evaluated 150 patients young adults. When compared the types of stroke, the greater frequency of ischemic stroke in this study corroborates to what has been described in the literature 3,4,18,19,22 , in particular, the proportion of patients diagnosed with hemorrhagic stroke were mostly of hypertensive etiology, reasoning with the findings of previous studies 3,4 . There was a statistically significant difference when comparing female and male with hypertensive etiology of hemorrhagic stroke: the most hypertensive were men, presenting higher frequency of hemorrhagic stroke.…”
supporting
confidence: 92%
“…The higher frequency of females observed in this study, confirms the research conducted on national territory 3,6,10 , including a study in the city of Salvador…”
supporting
confidence: 91%
“…Na atualidade não existe um consenso na literatura quanto à idade limite para considerar AVC no adulto jovem, estudos variam entre 45 e 60 anos (Cardoso, Fonseca, & Costa, 2003;Gomes et al, 2008;Zétola et al, 2001). A média de idade dos participantes deste estudo foi de 37,6 anos, cabe ressaltar que a faixa etária estabelecida para este pesquisa foi entre 18 e 45 anos.…”
Section: Discussionunclassified